2021
DOI: 10.1109/tse.2019.2891715
|View full text |Cite
|
Sign up to set email alerts
|

App Store Effects on Software Engineering Practices

Abstract: In this paper, we study the app store as a phenomenon from the developers' perspective to investigate the extent to which app stores affect software engineering tasks. Through developer interviews and questionnaires, we uncover findings that highlight and quantify the effects of three high-level app store themes: bridging the gap between developers and users, increasing market transparency and affecting mobile release management. Our findings have implications for testing, requirements engineering and mining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 91 publications
(100 reference statements)
1
61
0
1
Order By: Relevance
“…In this paper we empirically observe how five textual feature extraction techniques perform when used as clustering input, applied on the case of mobile app descriptions. We specifically select the baseline techniques that are most commonly used in Software Engineering research as reported by Arnaoudova et al (2015) and discussed in Section 5.…”
Section: Text Representation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we empirically observe how five textual feature extraction techniques perform when used as clustering input, applied on the case of mobile app descriptions. We specifically select the baseline techniques that are most commonly used in Software Engineering research as reported by Arnaoudova et al (2015) and discussed in Section 5.…”
Section: Text Representation Techniquesmentioning
confidence: 99%
“…Extracting features is also useful for the task of tackling and analysing user reviews. This aims to guide developers in sorting app reviews into bug reports and/or feature requests (or a variation of this taxonomy) which developers believe can be challenging (AlSubaihin et al 2019). Research also looked into collating user feedback into specific issues/features to help prioritise and summarise the large amount of feedback.…”
Section: Apps' Feature Extraction From Artefacts Written In Natural Lmentioning
confidence: 99%
“…Harman et al introduces two relevant topics: app store analysis app testing and optimisation [9], yet does not discuss possible relationships between these topics. Sibaihin et al discusses alpha and beta testing by humans using facilities provided by the app store [1]; their paper does not cover pre-launch testing, other release management tools, or Android Vitals.…”
Section: Related Workmentioning
confidence: 99%
“…As figure 1 shows, Android Vitals collects usage and run-time data from Android devices running Google Mobile Services 1 , from users who agreed to provide diagnostic data. It is available to Android developers who have active apps in Google Play; these developers can provide granular access to other people who have a valid Google Account.…”
Section: Introductionmentioning
confidence: 99%
“…App reviews is a rich source of user opinions [1,2,14,17]. These opinions can help developers to understand how users perceive their app, what are users' requirements, or what are users' preferences [1,2,14]. Not surprisingly, knowing user opinions is an important information need developers seek to satisfy [2,4].…”
Section: Introductionmentioning
confidence: 99%